Pengetahuan dan Sikap Lansia tentang Penggunaan Obat Tradisional Hipertensi - Awaluddin Awaluddin; Purwanto Purwanto (Poltekkes Kemenkes Bengkulu, 2019)
The used of traditional medicines to decrease hypertension were increased. The used of them were influenced by knowledge and attitude. The purpose of this study was to known the correlation of knowledge and attitude of the elderly in use of the traditional medicine to reducing hypertension in Batang Tumu Health Center, District of Indragiri Hilir. This study was analytical withcross sectionaldesign. The population were all elderly who had hypertension as many as 143 respondent. The number of samples in this study were 59 respondents. The technique of sampling was purposive. Measuring instrument used was questionnairre. The results showed that elderly with well knowledge were 31 respondents (52.2%) and positive attitude were 38 respondents (64.4%). The chi square test results showed that there was a significant correlation between knowledge with the use of traditional medicine to reduce hypertension with p value 0.002<alpa 0.05. There was a significant correlation between elderly attitude with the use of traditional medicine to reduce hypertension with p value 0.004 <alpa 0.05. This result of study had implication to nursing that needed good knowledge and positive attitude for elderly so that can be use hypertension traditional medicine.